Perception of José Ortega y Gasset’s Works in Essays of Oksana Zabuzhko - Shevchenko, Tetiana; Shapovalenko, Nadiia; Sytko, Olena; Susol, Liliia (Տիգրան Մեծ)
The article analyzes the peculiarities of the reception of Jose Ortega y Gasset‟s works in the essays of Oksana Zabuzhko. Emphasis is placed on the commonality of creative origins and ideas of both authors. The intellectual and poetic connections of iconic works are analyzed, particularly “The Revolt of the Masses” and “Notre Dame d‟Ukraine. Ukrainian woman in the conflict of mythologies”. The uniqueness of the ideas of the Spanish thinker in the construction of the concept of Ukrainian identity by Oksana Zabuzhko is emphasized. Itis concluded that the works of Jose Ortega y Gasset are analyzed and inter-twined with the work of Oksana Zabuzhko regarding socio-political and poetic aspects. The format of the mega-essay, common for both authors, chosen for the presentation of their reflections, is objectively ana-lyzed. This format is a harmonious, highly artistic formation in which the content and form are balanced: here, all sections (parts) are logically and consistently connected, placed in a cause-and-effect relationship. Both artists chose the method of “philosophizing in the space of literature”, aestheticized intellectualism, and enriched rational analysis of art and history, which allowed readers to get closer to the essence of Spanish / Ukrainian civilizations.
Keywords: Philosophy of language; Philosophy of literature